Pengaruh Teknologi Informasi, Kompetensi dan Independensi, terhadap Kualitas Audit Dengan Etika Auditor sebagai Variable Mediasi - David Nehemia Sabarwan; Hexana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
evaluating the competence and independence of auditors in order to ensure audit quality. While information technology may not directly impact audit quality, it does have a significant effect on auditor ethics. Additionally, the study finds that auditor ethics plays a crucial role in determining the overall audit quality. Strengthening the auditor ethics intervention further enhances the effect of information technology on audit quality. However, the competence and independence of auditors do not have a significant impact on audit quality, regardless of the auditor ethics intervention. These findings emphasize the need to focus on auditor competence, independence, and ethics to maintain and improve audit quality, and highlight the potential benefits of integrating information technology in auditing processes.